Peningkatkan Kinerja Guru dalam Pengembangan Evaluasi Hasil Belajar Melalui Supervisi Akademis di SMP Negeri 3 Kota Tangerang Selatan Tahun Pelajaran 2022-2023 - Nofiardi, Nofiardi (LAP4B, 2024)
The purpose of this school action research (PTS) is to determine the extent of coaching principals through academic supervision to improve teacher performance in the development of learning outcome evaluation. The method used is the Classroom Reasearch method (Action Research) which is carried out in 3 cycles, with each cycle consisting of problem formulation, action implementation, observation/data collection, and reflection. The results of the actions taken are proven to improve teacher performance by achieving ideal standards. From an average of 62.02 teacher performance in cycle I, it can increase to 73.10 in cycle II, and 81.31 in cycle III.Teacher completeness is 28.57% in cycle I, to 66.67% in cycle II, and 100% in cycle III. These results show that coaching through the academic supervision of the principal can improve teacher performance in the development of learning outcome evaluation with completeness reaching 100%